High-riding inominate artery: Challenge during tracheostomy - Wannitta Wong, E-Ting; Saniasiaya, Jeyasakthy; Tharek, Anas; Sallehuddin, Nur Syazwani (Springer Science and Business Media LLC, 2023)
An aberrant vessel presenting as a pulsatile neck mass poses a significant challenge intraoperatively if overlooked during the pre-operative period. We present a case of a high-riding innominate artery (HRIA) just above the suprasternal notch, with the right common carotid artery crossing the midline just inferior to the thyroid gland in a 72-year-old lady referred for tracheostomy. The surgeon operating on the anterior part of the neck must be aware of the HRIA and equipped with sufficient knowledge of interventions that may be adapted to prevent injury. We aim to highlight the importance of careful investigations of subtle signs which may lead to the diagnosis and treatment with a review of various interventions for this unusual condition.